Implementation The Theory Of Planned Behavior Model As Behavior Reinforcement For Agent Of Change As An Effort To Improve Corruption Prevention At SMA Taruna Akterlis Medan - Mukidi Mukidi; Nelvitia Purba; Muhlizar Muhlizar; Humala Sitinjak (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
During the Covid 19 Pandemic, which occurred in all countries in the world, without exception in Indonesia, experiencing a period of economic crisis, the fact is that corruption still occurs. Deviate from the applicable rules and do not have a sense of humanity. Eradication of corruption is carried out by taking action and prevention, this prevention will never work optimally if it is only carried out by the government without involving the younger generation as one of the most important parts, this is because it is the future heir of anti-corruption in strengthening behavior in everyday life. The role of the younger generation is focused on preventing corruption by participating in building an anti-corruption culture in society.The research method used is normative juridical-empirical. The analysis carried out in this study using descriptive qualitative analysis. The experimental design model to test the product that has been designed for this research has made the method and after being corrected by the researcher through discussions with experts in this research field, population and sample testing as well as data instruments in the study will be carried out. Improving this product can be done by presenting several experts who are experts in this research field to assess whether the model design has been made by the researcher. So that you can identify your strengths and weaknesses. This design validation is carried out through discussion forums and seminars that will focus on product improvement by testing with experts and practitioners.Research Results It can be stated that: The Theory Of Planned Behavior Model As Strengthening Agent Of Change Behavioral Education For The Young Generation As An Effort To Prevent Corruption. The success of this model can be revealed through Theory of Planned Behavior. The end result is expected that individuals/students have a great possibility to adopt a behavior that is character building including honesty, discipline, hard work. If the individual/young generation has a positive attitude towards this behavior, then in this case the whole of the young generation who are close and related to this behavior will be able to do well and as an agent of change make the younger generation an asset of the nation to change a country that is there is a lot of corruption to become a country free from corruption. Based on the description above, the Theory of Planned Behavior is expected. The final result is expected that individual TAMA SMA students in Medan City have a great possibility to adopt a behavior, namely character building including honesty, discipline, hard work. If the individual/young generation has a positive attitude towards this behavior, then in this case the whole of the young generation who are close and related to this behavior will be able to do well and as an agent of change make the younger generation an asset of the nation to change a country that is there is a lot of corruption to become a country free from corruption.